Atlas of European values – Making DATA accessible for educational use - Krause, Uwe (Sens public, 2009)
The European Values Study is a longitudinal research project about human values and resulted in an atlas published by the University of Tilburg. Fontys University of Applied Sciences Tilburg is responsible to make the scientific data accessible for educational use and develop teaching materials for secondary schools and higher education. At the moment European and world maps as well as assignments are available in four languages: Slovak, English, German and Dutch. See also www.atlasofeuropeanvalues.eu